Experimental study on the feasibility and thermal performance of a multifunctional air conditioning system using surplus air thermal energy to heat a Chinese solar greenhouse. (October 2022) - He, Xueying; Wang, Pingzhi; Song, Weitang; Wu, Gang; Ma, Chengwei; Li, Ming
Abstract: Maintaining a suitable temperature in the greenhouse in the cold season requires the assistance of the heating system, and renewable energy is advocated to replace traditional energy for greenhouse heating. To adjust the microclimate of the greenhouse, this study proposed a multifunctional air conditioning system that utilizes surplus air thermal energy (SATE), and the heat balance is used to calculate the system performance required for heating. Experimental results show that the system increased the minimum air temperature at night by 2.8 °C, and it also improved in continuous cloudy days, making the greenhouse temperature and humidity at night closer to suitable conditions, and the air temperature is more uniform in time and space. The provided heat energy and heat transfer rate of the multifunctional air conditioning system were 168.8 MJ/d and 4289 W, respectively, which were 95% of the Chinese Solar Greenhouse (CSG) heat demand and 50% of the CSG maximum heat load. Adjusting the temperature difference between water and air can also improve the heat release capacity of the system, and the system still has great potential. The multifunctional air conditioning system heating CSG is feasible, and the system is environmentally friendly and energy-saving, suitable for all kinds of greenhouses, and will have broad application prospects.